Physical variables that explain alluvial soil variability and their spatial behavior - Jaramillo, Daniel Francisco; Gómez, María Luisa Anaya; Restrepo Mona, Carlos Andres; Sánchez, Hugo Alberto González; Mejía, Fernando Álvarez (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to use the principal component and semivariance analyses to select physical variables that could explain the variability of an alluvial soil, in order to establish the spatial behavior of the chosen variables so that the location of experimental plots could be technically defined to study the abrasiveness effect on the wearing away of farm equipment. Field tests were performed in 2008, on a 6,000 m2 flat lot with medium to heavy soil texture (Vertic Haplustepts). An intensive sampling was done in a grid of 10x14 m. The variables which had the most weight on the first three principal components were the contents of silt, fine and intermediate sand, intermediate gravel, soil moisture at field capacity, and the hygroscopic coefficient. Except for the half sand and the field capacity, the other properties showed a high spatial dependence, and their distribution showed that in the experimental plot there are three sectors of differential accumulation of silt and fine sand. The combination of principal component analysis and geostatistics allowed for defining the soil properties involved in the wear of tools, their spatial pattern and the most appropriate way of distributing plots to study soil abrasiveness.